Management of Open Globe Injury Followed by Cataract Traumatic and Corneal Laceration in a 37-year-old Man. A Case Report: Poster Presentation - Case Report - General practitioner - Martyana, dr Diana Eka; Kusumastuti, Diana Haryati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular trauma is the most common cause of visual impairment and unilateral vision loss. According to the Birmingham Eye Trauma Terminology, ocular trauma consists of Open Globe Injury and Closed Globe Injury. Open globe injury is a full-thickness eyewall wound due to a laceration or occult rupture. Damage to the cornea and lens are among the most common types of ocular trauma. Case Illustration : This case report involves a 37 year-old-man who presented with complaints of pain and visual impairment in the left eye for the past month. The symptoms appeared after accidentally getting hit by a bamboo branch. Upon examination, the patient had a visual acuity of 1/300 in the left eye, ciliary injection (+), non-spherical pupil, and normal intraocular pressure on palpation. On slit lamp examination, a 7mm corneal laceration with a scar formation and a lens mass in the eye's anterior chamber. Discussion : In this case, the open globe injury resulted in visual impairment due to corneal laceration and traumatic cataracts. The trauma occurred one month before the examination, and the corneal laceration had already formed a leukoma. The patient underwent corneal repair and vitrectomy, extracapsular cataract extraction using the ECCE technique, and intraocular lens implantation. Conclusion : The prognosis of ocular trauma depends on the severity of the injury to the eye structures, the time between the injury and surgery, the preoperative visual acuity, the mode of injury, and the patient's age. The OTS scoring system can predict the final visual acuity outcome in such cases.